Pengaruh Diethyl Ether Terhadap Torsi dan Daya Mesin Diesel Injeksi Langsung Berbahan Bakar Solar Campuran Jatropa (Infotekmesin, 2020)
Increasing consumption of fossil fuels, depleting oil reserves and increasingly expensive fuels have forced the use of alternative fuels. Diethyl ether (DEE) can be used as an alternative fuel because it has a high cetane number, low viscosity, and high oxygen content. This observation was carried out to determine the effect of the addition of Diethyl ether on 20% diesel-jatropha fuel mixture to the torque and power produced. Tests carried out on a 4JB1 type direct injection diesel engine with a constant speed of 2500 rpm. The DEE volume used is 5%, 10%, and 15% is volume-based. The test results show 20% jatropha content produces lower torque and power compared to pure diesel fuel (D100). Also, the addition of DEE to 20% diesel-jatropha fuel produces low torque and power but the value is higher than 20% of diesel-jatropha fuel. The highest torque and power reduction trends occurred in the use of DJ20 fuel by 0.0448% when loading 25%. While the lowest decrease in torque and power occurs in the DJ20DEE15 fuel by 0.0112% with 100% loading compared to D100 fuel.